What would Batman do? Self‐distancing improves executive function in young children. Issue 3 (21st May 2015) - White, Rachel E.; Carlson, Stephanie M.
Abstract: This experimental research assessed the influence of graded levels of self‐distancing – psychological distancing from one's egocentric perspective – on executive function (EF) in young children. Three‐ ( n = 48) and 5‐year‐old ( n = 48) children were randomly assigned to one of four manipulations of distance from the self (from proximal to distal: self‐immersed, control, third person, and exemplar) on a comprehensive measure of EF. Performance increased as a function of self‐distancing across age groups. Follow‐up analyses indicated that 5‐year‐olds were driving this effect. They showed significant improvements in EF with increased distance from the self, outperforming controls both when taking a third person perspective on the self and when taking the perspective of an exemplar other (e.g., Batman) through role play. Three‐year‐olds, however, did not show increased EF performance as a function of greater distance from the self. Preliminary results suggest that developments in theory of mind might contribute to these age‐related differences in efficacy. These findings speak to the importance of psychological distancing in the expression of conscious control over thought and action from a young age and suggest a promising new avenue for early EF intervention. Abstract : Self‐distancing (by taking a third person perspective on the self or taking the perspective of an exemplar other) improved executive function in 5‐year‐olds, but not 3‐year‐olds. Preliminary evidence suggests that these age‐related differences could be attributable, at least in part, to improvements in theory of mind.